Comparison Study of Flow in a Compound Channel: Experimental and Numerical Method Using Large Eddy Simulation SDS-2DH Model - Nugroho, Eka Oktariyanto; Ikeda, Syunsuke (Journal of Engineering and Technological Sciences, 2007)
Flow modeling  in a compound channel  is a complex matter. Indeed, due to the smaller velocities in the floodplains than in the main channel, shear layers develop at the interfaces between two stage channels, and a  momentum transfer corresponding to this shear layer affects the channel conveyance. Since a compound channel  is characterized by a deep main channel flanked by relatively shallow flood plains, the interaction between the faster fluid velocities in the main channel and the slower moving flow on the floodplains causes shear stresses  at  their  interface  which  significantly  distort  flow  and  boundary  shear stress  patterns.  The  distortion  implies  that  flow  field  in  rivers  is  highly  non homogeneous  turbulent,  which  lateral  transport  of  fluid  momentum  and suspended sediment are influenced by the characteristics of flow in rivers. The nature of mechanism of lateral transport needs to be understood for the design of river engineering schemes that rely upon realistic flow. Furthermore,  the  flows  in  river  are  also  almost  turbulent.  This  means  that  the fluid  motion  is  highly  random,  unsteady,  and  three -dimensional.  Due  to  these complexities,  the  flow  cannot  be  properly  predicted  by  using  approximate analytical solutions to the governing equations of motion. With the complexity of  the  problems,  the  solution  of  turbulent  is  simplified  with  mathematics equation. The  momentum  transfer  due  to  turbulent  exchanges  is  then  studied experimentally and numerically. Experimental data is obtained by using ElectroMagnetic Velocimetry and Wave Height Gauge. The  Large  Eddy  Simulation  Sub  Depth  Scale  (LES  SDS)-2  Dimensional Horizontal (2DH) Model is used to solve the turbulent problem. Successive Over Relaxation (SOR) method is employed to solve the numerical computation based ob finite difference discretization. The model has been applied to the compound channel  with smooth roughness. Some organized large eddies were found in the boundary  between  main  channel  and  flood  channel.  At  this  boundary  the transverse  velocity  profile  exhibits  a  steep  gradient,  which  induces  significant mass and momentum exchange, acts as a source of vorticity, and  generates high Reynolds stresses. The  Large  Eddy  Simulation  SDS-2DH  model  enables  to  predict  quite successfully  the  wavelength  of  some  observed  vortices.  The  estimated  vortex wavelengths agree again with the measurements and the theoretical predictions. The present model is proven to be a useful tool for engineering applications, as it can simulate the dynamic development of large eddies.